NUMERICAL TECHNIQUES TO DETERMINE THE UTD BISTATIC CREEPING WAVE PATHS AND PARAMETERS FOR AN ELLIPSOID - Choi, Jaehoon (Applied Computational Electromagnetics Society Journal (ACES), 2022)
In applying the Uniform Geometrical Theory of Diffraction (UTD) to evaluate the scattering patterns of a doubly curved surface, the determination of correct ray paths is one of the most important and difficult tasks. In this paper, an efficient numerical technique to obtain the complete ray path of the creeping wave for the bistatic scattering of an ellipsoid is discussed. Also, the numerical method to evaluate the energy spreading factor of the creeping wave and the caustic distance at the diffraction (launching) point are described. An ellipsoid is chosen because of its modeling capability to represent the fuselage of an aircraft and similar objects. The same numerical techniques for an ellipsoid can be extended to a general doubly curved surface as well. [Vol. 6, No. 1, pp. 140-158 (1991), Special Issue on Applicatlons of High Frequency Methods and Computer Techniques in Electromagnetics]